Impact Resistance of High Strength Steels. (2016) - Mazur, Magdalena; Mikova, Katarina
Abstract: Based on own research and data from the manufacturer there were presented material characteristics of the steel Hardox (400 and 450) and Domex 700MC. Nowadays this steel is more and more used in design of modern semi trailers constructions. High mechanical properties and durability of this type of steel are its advantage. The combination of these features enables the construction of lighter semi-trailer's components, which would result in a semi-auto with a lower weight of its own. This paper summarizes the results of research with the results made available by the manufacturer SSAB Company.